KAJIAN YURIDIS PENGATURAN HUKUM TINDAK PIDANA PENCURIAN DATA PRIBADI (PHISING) DI INDONESIA - Darmilis Darmilis; Lola Yustrisia; Riki Zulfiko (Ensiklopedia of Journal, 2023)
Personal data theft in Indonesia, with several high-level data breaches throughout 2022 to 2023. The urgency of this problem is highlighted by the fact that Indonesia has just passed its first comprehensive data protection law in 2022. Previously the regulations used were regulations from the minister of communication and informatics number 20 of 2016 concerning protection of personal data in electronic systems. The lack of legal regulations in Indonesia regarding the protection of personal data has been identified as a problem. The new law is critical in maintaining public trust, especially since personal information has been compromised in previous security breaches. The law requires entities that handle personal data of Indonesian residents to ensure data protection in their systems. The urgency of personal data theft in Indonesia is increasingly clear by the fact that Indonesia is ranked third as the country most affected by data breaches in the second quarter of 2022. The impact of personal data theft in Indonesia is very significant and far-reaching. This study uses the normative juridical research method, which is legal research conducted by examining literature or secondary data as a basis for research by conducting a search of regulations and literature related to the problem under study. Using descriptive research specifications and data collection techniques using library research with qualitative data analysis methods. The results of the research in this study are the legal arrangements regarding the crime of personal data theft in Indonesia and the characteristic forms of the crime of personal data theft in Indonesia. In conclusion, personal data theft in Indonesia has significant implications for society, including loss of trust, financial loss, legal implications, cybersecurity risks, social media risks, and reputational damage. The new personal data protection law is an important step in addressing this problem and protecting the personal data of Indonesian residents.